Strategies for converting landfill gas to renewable energy and renewable feedstock: synergy with the hydrocarbon industry - Fang, Jian; Lou, Helen H.; Kolp, Andrew; Chen, Daniel (Frontiers in Energy Research, 2024)
Landfills are major emitters of greenhouse gases, especially methane (CH4). To address this, the U.S. EPA promotes utilizing landfill gas (LFG) for renewable energy. Our study in Southeast Texas compared four LFG conversion strategies: flaring, electricity generation, renewable natural gas (RNG), and methanol production. Scenario analysis was conducted to reveal the influence of market conditions and incentives on profitability. While electricity generation consistently yielded the highest returns, methanol production emerged as a close contender due to the strategic advantage of its proximity to the landfill site in this industrial zone. This study highlights the promising synergy between landfills and the hydrocarbon industry for sustainable development.